A model for ageing-home-care service process improvement - Shu-Yan Yu; An-Jin Shie (International Journal of Management, Economics and Social Sciences (IJMESS), 2017)
The purpose of this study was to develop an integrated model to improve service processes in ageing-home-care. According to the literature, existing service processes have potential service failures that affect service quality and efficacy. However, most previous studies have only focused on conceptual model development using New Service Development (NSD) and fail to provide a systematic model to analyse potential service failures and facilitate managers developing solutions to improve the service process. This study proposes a model that integrates service blueprinting and Failure Mode Effect Analysis (FMEA). First, the service blueprint tool was used to analyse potential service failures in the service process. Then, FMEA was employed to diagnose the possible causes and effects of service failures in the model. Finally, we utilised the expert brainstorming method to develop feasible solutions to improve the service process. A case study of the service process used by an ageinghome-care service agency was conducted to demonstrate the applicability of the proposed model. Finally, we summarised the advantages of the proposed model and its implications.
Keywords: 330; Ageing-home-care service; service process; service blueprint; failure models and effects analysis (FMEA)